Mitochondrial Dysfunction and Disturbed Coherence: Gate to Cancer - Jiří Pokorný; Jan Pokorný; Alberto Foletti; Jitka Kobilková; Jan Vrba; Jan Vrba (MDPI AG, 2015)
Continuous energy supply, a necessary condition for life, excites a state far from thermodynamic equilibrium, in particular coherent electric polar vibrations depending on water ordering in the cell. Disturbances in oxidative metabolism and coherence are a central issue in cancer development. Oxidative metabolism may be impaired by decreased pyruvate transfer to the mitochondrial matrix, either by parasitic consumption and/or mitochondrial dysfunction. This can in turn lead to disturbance in water molecules' ordering, diminished power, and coherence of the electromagnetic field. In tumors with the Warburg (reverse Warburg) effect, mitochondrial dysfunction affects cancer cells (fibroblasts associated with cancer cells), and the electromagnetic field generated by microtubules in cancer cells has low power (high power due to transport of energy-rich metabolites from fibroblasts), disturbed coherence, and a shifted frequency spectrum according to changed power. Therapeutic strategies restoring mitochondrial function may trigger apoptosis in treated cells; yet, before this step is performed, induction (inhibition) of pyruvate dehydrogenase kinases (phosphatases) may restore the cancer state. In tumor tissues with the reverse Warburg effect, Caveolin-1 levels should be restored and the transport of energy-rich metabolites interrupted to cancer cells. In both cancer phenotypes, achieving permanently reversed mitochondrial dysfunction with metabolic-modulating drugs may be an effective, specific anti-cancer strategy.